Coeficiente do tanque Classe A obtido por diferentes métodos em ambiente protegido e no campo - Cunha, Antonio Ribeiro [UNESP] (Universidade Estadual de Londrina (UEL), 2011)
There are several methods for determining the Class-A pan coefficient (Kp) to estimate the reference evapotranspiration (ETo), which is of great importance to water management in agriculture. Most of these methods take into account the wind speed, relative humidity and the fetch area. This study was done in region of Botucatu, SP, in greenhouse and field in the months of July-August (dry) and September-October (rainy), used the methods of Doorenbos e Pruitt (1977), Cuenca (1989), Snyder (1992), Pereira et al. (1995), Allen et al. (1998) and correlation between ETo determined by Penman-Monteith (EToPM) and evaporation of the Class-A pan (ECA). The EToPM was used as standard for the correlations between the ETo determined by the Class-A pan (EToTCA) obtained by different methods of Kp. The Kp in greenhouse ranged between 0.51 and 0.85, and in the field from 0.33 to 0.85. The methods of Allen et al. (1998) and Snyder (1992) are the most recommended for dry months in greenhouse and rainy months the correlation between the ECA and EToPM e Cuenca (1989). In the field condition, the methods of Allen et al. (1998) and of correlation between the ECA and EToPM for dry months, and for rainy months of Allen et al. (1998) and Cuenca (1989). The method of Allen et al. (1998) was the most efficient, regardless of the environment and of months analyzed. The fixed value of Kp should only be used when it is not possible to determine from its more sophisticated methods.
Calculation of the Class-A pan coefficient in greenhouse and field by different methods
Keywords: Evapotranspiration; Irrigation management; Greenhouse